A Case Report of Wilson Disease with Neurological Features (Extra Pyramidal Symptoms) & Psychiatric Disorders (Mood & Behavioral) - Dr Aaemal Aziz Jabarkhil, (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2019)
Wilson disease is a genetic disorder with an autosomal recessive pattern of inheritance. It is due to an error of copper metabolism with the major presentations of changes in liver, Central nervous system, Eye and occasionally other organs.ATP7B is the gene product of the Wilson disease gene located on chromosome 13 and resides in hepatocytes transporting copper into the secretory pathway for incorporation.The disease can be early seen in childhood or early adolescences, and the prevalence for the hepatic and nervous features are equal.The neurotic features of Wilson disease reflect the morbidity of caudal nucleus, putamen, cerebral cortex and cerebellum. Neurological signs include tremor, chorea like movements, spasticity, akinetic, dysarthria, dysphagia, abnormal body posture and ataxia. Psychiatric disorders accompany the disease are Dementia, Affective disorder, behavioral, Personality changes and rarely psychosis.Laboratory exams conclude the determination of copper level in 24 hour collected urine and blood serum, Ceruloplasmin level, biopsy of the liver and brain imaging.In case of neurotic disorders, one should keep in mind the differential diagnosis with multiple sclerosis and Huntington. The treatment is supportive and the best way is to clear the copper from the body is still controversial, but a copper level absorber from the body tissues is used these days. Early treatment will partially or completely help with cure of the disease. On the other hand the disease will progress and is fatal. Liver transplantation is necessary in cases of liver failure.The asymptomatic patients of Wilson disease should undergo evaluation for Wilson disease. We hereby report a case of Wilson disease that was found in a 19 year old boy in Ali Abad teaching hospital department of neuropsychiatry back in February 2019.The clinical features found were extra pyramidal, dystonia, Kyser Fleischer rings in eyes and psychiatric (behavior and mood) disorders, and with the help and detection of copper and Ceruloplasmin levels in blood serum the diagnosis of Wilson was made in this boy.We advised a copper level absorber (Penicillinium) and the cessation of copper. With these measures we found an improvement of the patient’s condition in 4 months.